Optimization of reproduction of ricefish endemic to Southeast Sulawesi Oryzias woworae Parenti & Hadiaty, 2010 through different sex ratios in spawning - Mohamad Ayip Firmansyah; Mustahal Mustahal; Mas Bayu Syamsunarno; Muh Herjayanto (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Oryzias woworae has a beautiful color and has been traded as ornamental fish. This species is an endemic ricefish from Muna Island, Southeast Sulawesi, and is threatened with endangered status. Information on the optimal spawning sex ratio in O. woworae is unknown. This study aimed was to examine the optimization of reproduction based on the sex ratio of male: female broodstock O. woworae involved in spawning. The sex ratio of male: female spawning broodstock used were 1:1, 1:2, 1:3, and 1:4. The male and female brooders used had a total length of 3,1 ± 0,5 cm and 2,5 ± 0,5 cm. After adaptation, the broodstock of O. woworae was put into aquariums according to the treatment, and each container contained three spawning substrates. The harvesting of eggs on the substrate is carried out two times a day. The results showed that spawning O. woworae with a ratio of 1♂: 4♀ produced the lowest number of eggs and was significantly different with ratios of 1♂: 1♀ and 1♂: 2♀ (P<0,05). The ratio of 1♂ : 3♀ gave the highest egg hatching of 55% but was not significantly different from other treatments (P>0,05). The difference in male and female ratios did not affect the survival rate of O. woworae larvae (P>0,05), with values from 91,9-100%. The highest larvae produced was found in the spawning ratio of 1♂ : 3♀ with 37 larvae but not significantly different from other treatments (P>0,05). The water quality values during the study were temperature 26,5-310C, pH 5,5-8,8, and dissolved oxygen 5,3-6,0 mg L-1. O. woworae broodstock spawning can be optimized with a male to female ratio of 1:3. Abstrak Oryzias woworae memiliki warna indah dan telah diperjualbelikan sebagai ikan hias. Spesies ini merupakan jenis ikan padi endemik dari Pulau Muna, Sulawesi Tenggara yang statusnya terancam punah. Informasi mengenai nisbah kelamin pemijahan optimal pada ikan O. woworae belum diketahui. Tujuan penelitian ini untuk mengkaji optimasi reproduksi berdasarkan nisbah kelamin induk jantan : betina O. woworae yang terlibat dalam pemijahan. Perlakuan nisbah kelamin pemijahan induk jantan ♂ : betina ♀ yang digunakan yaitu 1:1, 1:2, 1:3, dan 1:4. Induk jantan dan betina yang digunakan mempunyai panjang total yaitu 3,1 ± 0,5 cm dan 2,5 ± 0,5 cm. Setelah diadaptasikan, induk O. woworae dimasukkan ke dalam akuarium sesuai dengan perlakuan dan setiap wadahnya telah berisi tiga substrat pemijahan. Pemanenan telur pada substrat dilakukan setiap hari pada pagi dan sore hari. Hasil penelitian menunjukkan pemijahan ikan O. woworae dengan nisbah 1♂ : 4♀ menghasilkan jumlah telur yang terendah dan berbeda nyata dengan nisbah 1♂ : 1♀ dan 1♂ : 2♀ (P<0,05). Penetasan tertinggi terdapat pada nisbah 1♂ : 3♀ yaitu 55% namun tidak berbeda nyata dengan perlakuan lainnya (P>0,05). Perbedaan nisbah kelamin jantan dan betina tidak memengaruhi sintasan larva O. woworae (P>0,05), dengan nilai berkisar antara 91,9-100%. Jumlah larva dihasilkan tertinggi terdapat pada nisbah pemijahan 1♂ : 3♀ dengan 37 ekor larva namun tidak berbeda nyata dengan perlakuan lainnya (P>0,05). Nilai kualitas air selama penelitian yaitu suhu 26,5-310C, pH 5,5-8,8, dan oksigen terlarut 5,3-6,0 mg L-1. Pemijahan ikan O. woworae dapat dioptimalkan dengan perbandingan jantan dan betina sebesar 1:3.